LA EDUCACION EN EL SIGLO XX - Palacios, Jesús (CUADERNOS EDUCATIVOS ;, 1997)
V.1 LA TRADICION RENOVADORA [ROUSSEAU, FERRIERE, PIAGET, FREINET].-- V.2 LA CRITICA ANTIAUTORITARIA [FERRER, NEILL, ROGERS, LOBROT, OURY, VASQUEZ].-- V.3 LA CRITICA RADICAL [MARX, ENGELS, MAKARENKO, BLONSKIJ, GRAMSCI, BOURDIEU, PASSERON, BAUDELOT, ESTABLET, ALTHUSSER]